Perceived Parental Affection, Supervision and Social Media Addiction of Chittagong University Students (Chittagong University Journal of Biological Sciences, 2024)
Parenting behaviors like parental affection and supervision greatly determine different developmental outcomes of a person. Inadequate parenting behavior can lead to different behavioral problems, even various forms of addictions such as social media addiction in young adults like university students. The present study attempted to investigate the relation of social media addiction with parental affection and supervision of university students according to their gender and family type. The sample of the study was purposively selected 300 students from Chittagong University. The family relation scale and the Bangla version of Bergen Social Media Addiction Scale were used as data collection tools. The collected data were analyzed by using independent sample t-test, Pearson product moment correlation and regression analysis. Male participants perceived significantly more affection and supervision than female participants. Participants from nuclear family had significantly more social media addiction than extended family. Social media addiction was found significantly negatively correlated with both parental affection and supervision. Parental affection significantly predicted social media addiction. The findings of the study may contribute to reduce social media addiction of our university students by highlighting the need for proper parental affection and supervision.Chittagong Univ. J. B. Sci. Vol. 12 (1 & 2): 72-82, 2024